Artes de curar em confronto? disputas, ofícios e práticas de cura na Paraíba Imperial (1870-1880) - Silva, Wuendisy Fortunato da (2020)
The objective of this study is to analyze the circumscribed universe of the arts of healing in Paraíba in the Imperial period, taking as time frame the years that form the decades of 1870 and 1880, whose period marks a gradual increase in the number of curators in action, especially those who received the name common of “healing practitioners”, a group that includes healers, bleeding barbers, apothecaries, among others. To this end, it will take as a foundation the discussions listed from the perspectives followed by the History of Health and Diseases, giving special emphasis to the questions that, within these perspectives, focus their analysis on the discussions that deal with the arts of healing. In this sense, it was aimed to understand the functioning of the disputes that occurred between the different agents of healing and, above all, how these were formed and endorsed over time, as well as the paths through which the so-called scientific and academic medicine in the period ended up validating a power strategy that would yield its multiple influences in the face of society and its socio-cultural habits in front of several different traditional healers. To this end, it will be used a strategic and varied documentary corpus, which includes historical sources such as the Reports of the Presidents of the Paraíba Province, the Reports of the Paraíba Health Inspectorate, memorialist reports, practical health guides circulating in the period, budget requests aid committees in provincial towns and cities, as well as opinions from the Presidential Palace of the Province of Parahyba do Norte, and some of the newspapers of the period. It is based on these sources that we will start from a theoretical-methodological perspective that mixes possibilities between different branches of Cultural History in interfaces with specific segments of Social History of Health. The verticalizations around this approach will allow us to contemplate with more clarity, an approach that puts on the agenda for verisimilitude, since health care; the division of functions that configured the different offices of healing; as well as the understandings about the disease and the experience of their experience in Paraíba in the 19th century, are possible topics to be perceived from certain theoretical and methodological instruments focused specifically on the circumscribed regional segment, therefore this work is inserted in the conceptual segment of historical culture that conceives reflections about history and regionalities.